Evolution of pulmonary inflammation and nutritional status in infants and young children with cystic fibrosis. Issue 5 (12th March 2011) - Ranganathan, Sarath C; Parsons, Faith; Gangell, Catherine; Brennan, Siobhan; Stick, Stephen M; Sly, Peter D; ,
Abstract : Introduction: Improved nutrition is the major proven benefit of newborn screening programmes for cystic fibrosis (CF) and is associated with better clinical outcomes. It was hypothesised that early pulmonary inflammation and infection in infants with CF is associated with worse nutrition. Methods: Weight, height and pulmonary inflammation and infection in bronchoalveolar lavage (BAL) were assessed shortly after diagnosis in infants with CF and again at 1, 2 and 3 years of age. Body mass index (BMI) was expressed as z-scores. Inflammatory cells and cytokines (interleukin 1β (IL-1β), IL-6, IL-8 and tumour necrosis factor α (TNFα)), free neutrophil elastase activity and myeloperoxidase were measured in BAL. Mixed effects modelling was used to assess longitudinal associations between pulmonary inflammation, pulmonary infection ( Staphylococcus aureus and Pseudomonas aeruginosa ) and BMI z-score after adjusting for potential confounding factors. Results: Forty-two infants were studied (16 (38%) male; 39 (93%) pancreatic insufficient); 36 were diagnosed by newborn screening (at median age 4 weeks) and six by early clinical diagnosis (meconium ileus). Thirty-one (74%) received antistaphylococcal antibiotics. More than two-thirds were asymptomatic at each assessment. Mean BMI z-scores were −1.5 at diagnosis and 0.5, −0.2 and −0.1 at 1, 2 and 3 years, respectively. Neutrophil elastase and infection with S aureus were associated with lower BMI, whereas age (p=0.01) and antistaphylococcal antibiotics (p=0.013) were associated with increased BMI. On average, each log10 increase in free neutrophil elastase activity was associated with a 0.43 (95% CI 0.06 to 0.79) reduction in BMI z-score. Discussion: Early nutritional status is associated with the underlying pulmonary pathophysiology in CF, and better understanding of these relationships is required. Studies are required to assess whether interventions can decrease pulmonary inflammation and improve nutrition. Early surveillance will enable such targeted interventions with the aim of improving these important clinical outcomes.